Visualization of Conventional and Combusting Subsonic Jet Instabilities - Kozlov, Victor V.; Grek, Genrich R.; Litvinenko, Yury A. (SpringerBriefs in Applied Sciences and Technology, 2016)
Based on new information obtained on free microjets, this book explains the latest phenomena in flame evolution in the presence of a transverse acoustic field with round and plane propane microjet combustion. It gives an overview of recent experimental results on instability and dynamics of jets at low Reynolds numbers and provides the reader, step by step, with the milestones and recent advances in jet flow stability and combustion. Readers will also discover a clarification of the differences between top-hat and parabolic round and plane jet instability. Chapters demonstrate features of the interaction between jet and crossflow, and how experimental data testify to similarities of the perturbed flow patterns of laminar and turbulent round jets. A similar response of the jets to external acoustic oscillations is shown, as well as the peculiarities of the effect of a transverse acoustic field on downstream evolution of round and plane macro- and microjets. Basic features of round and plane, macro and micro jets' evolution affected by initial conditions at the nozzle outlet and by environmental perturbations are highlighted. Students of fluid mechanics will gain a solid foundation in hydrodynamic stability and combustion of subsonic jet flow and researchers will value the presentation of special aspects of instability and transition. The work treats both theoretical and practical facets, and it includes supplementary material such as PowerPoint multimedia notes based on results of laboratory scientific experiments.